2022
DOI: 10.3389/fpls.2022.976094
|View full text |Cite
|
Sign up to set email alerts
|

Full-length transcriptional analysis reveals the complex relationship of leaves and roots in responses to cold-drought combined stress in common vetch

Abstract: Plant responses to single or combined abiotic stresses between aboveground and underground parts are complex and require crosstalk signaling pathways. In this study, we explored the transcriptome data of common vetch (Vicia sativa L.) subjected to cold and drought stress between leaves and roots via meta-analysis to identify the hub abiotic stress-responsive genes. A total of 4,836 and 3,103 differentially expressed genes (DEGs) were identified in the leaves and roots, respectively. Transcriptome analysis resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…SMRT sequencing produces longreads and is particularly useful for non-model species for which whole-genome sequencing data are lacking [33,34]. With the continuous improvement of sequencing technology, the application of third-generation sequencing technology in the study of plant interaction is also very common [35][36][37]. Here, our results provide the first comprehensive, high-quality, full-length transcriptome of the sesame cultivars 'Henan No.1' and 'Jinzhi No.3' via a combination of SMRT-seq and RNA-seq, with correction of SMRT reads using Illumina reads.…”
Section: Discussionmentioning
confidence: 99%
“…SMRT sequencing produces longreads and is particularly useful for non-model species for which whole-genome sequencing data are lacking [33,34]. With the continuous improvement of sequencing technology, the application of third-generation sequencing technology in the study of plant interaction is also very common [35][36][37]. Here, our results provide the first comprehensive, high-quality, full-length transcriptome of the sesame cultivars 'Henan No.1' and 'Jinzhi No.3' via a combination of SMRT-seq and RNA-seq, with correction of SMRT reads using Illumina reads.…”
Section: Discussionmentioning
confidence: 99%
“…Seed germination and seedling emergence are important stages in the establishment of a plant species and the most sensitive ones in the plant's life cycle under environmental conditions [47]. In the context of global climate change, drought, salinity, and cold are the major adverse factors limiting seed germination and early establishment as well as subsequent growth and productivity [48][49][50]. In addition, burial depth is also one of the primary factors known to influence seedling emergence and establishment [51], and deep sowing resulted in mechanical stress on seeds and seedlings, which ultimately caused poor emergence performance and stand establishment [52].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have reported how horticultural crops respond to combined stresses containing drought and salt [43,44], drought and cold [45], etc. Despite the importance, studies are lacking and need attention to address the complex mechanisms underlying these stresses.…”
Section: Heat and Salinity Stressmentioning
confidence: 99%